(untitled) - Slater, J. C. (New York, 1939)
Provides the foundation needed for more advanced work in materials science. Ideal for a two-semester course, the text focuses on chemical bonding, crystal structure, mechanical properties, phase transformations, and materials processing for the first semester.
Keywords: Chemistry, Physical and theoretical,Lý thuyết hóa lý